2006
DOI: 10.1267/ahc.06016
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PERF 15 mRNA in Tissue Sections from Rat Testes

Abstract: We previously conducted basic research to quantify in situ hybridization (ISH) signals in rat testes. In this experimental model, we selected ribosomal RNA (rRNA) as the hybridizable RNA in paraffin sections, since it allowed us to easily analyze ISH signals expressed with digoxygenin (DIG)-labeled probes quantitatively through “posterization” of the images. We applied this method to analyze the quantification of transcript, PERF 15 mRNA. PERF 15 is expressed specifically in the testes and localized in the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The GnRH-I mRNA density value of each bird was obtained by calculating the mean density of ten randomly chosen cells in the brain section which had the largest numbers of GnRH-I neurons. Quantification of non-radioactive in situ hybridi-zation signal was validated as in previous studies (Ubuka et al 2005, Kogami et al 2006. GnRH-I mRNA density levels were compared between mature and immature female birds using Student's t-test.…”
Section: Image Processing and Statisticsmentioning
confidence: 99%
“…The GnRH-I mRNA density value of each bird was obtained by calculating the mean density of ten randomly chosen cells in the brain section which had the largest numbers of GnRH-I neurons. Quantification of non-radioactive in situ hybridi-zation signal was validated as in previous studies (Ubuka et al 2005, Kogami et al 2006. GnRH-I mRNA density levels were compared between mature and immature female birds using Student's t-test.…”
Section: Image Processing and Statisticsmentioning
confidence: 99%
“…However, useful information is limited to a relatively small group of studies that utilize non-isotopic hybridization and good fixation and present photographs in which the location of the hybridization signal can be visualized. All of these studies show no localization (Weitzel et al 2003, Iida et al 2004, Ellis et al 2005, Kogami et al 2006. In contrast, Fukuda et al (2004) reported that the MOR23 mRNA is localized close to the nucleus (chromatoid body?…”
Section: Introductionmentioning
confidence: 96%
“…The intensities of the signal of MeCP2 in epididymal duct, stromal cells and capillary endothelium of normal developing testis of (0- and 7-day-old) rats were analyzed by the one way ANOVA as described [ 10 ] to examine whether there were any statistical differences between the two groups. Twenty-five high-power fields for each of the three independent samples were evaluated.…”
Section: Methodsmentioning
confidence: 99%